A study of defects generation on NiCo substrate during electroplating and its minimisation through proper cleaning - Begum S.; Sambasivam K.; Ansari M.N.M.; Hashmi M.S.J. (Taylor and Francis Ltd., 2023)
There are numerous substrates that are electroplated in electronic industry to use in electronic devices. NickelCobalt (NiCo) is one of the substrates that is used in the integrated circuits for telecommunication. The substrate is needed to prepare before electroplating of which pre-cleaning is of paramount importance. The substrate must be cleaned to remove grease, oil, etc. from the surface. Moreover, the gold contaminant on the surface of NiCo substrate is transformed to gold oxide during heat treatment, which is a prerequisite step before electroplating. It was observed that standard pre-cleaning procedure practiced in the electronic industry cannot remove the oxide contaminant. Fairly controlled uniform thickness can be achieved by proper control of electroplating parameters. However, the defects generated on plated substrate cannot be eliminated by controlling electroplating parameters. It was found that pre-cleaning of substrate played an important role to eliminate the contaminants. Poor adhesion of plating materials, blistering, skip plating, plate flakes, pitting are a few common plating defects which result in poor solderability. In this review, electroplating and its defects and minimisation of defects are discussed. Surface preparation before plating is crucial in this respect. Defect-free substrate results in efficient solderability, consequently reducing rejection rate of substrate and increasing the yield, thereby, making the process cost effective. 2020, 2020 Informa UK Limited, trading as Taylor & Francis Group.